Begusarai Municipal Corporation : A study on population characteristics - Divya, Smriti; Yadava, R. S. (National Geographical Journal of India, 2022)
Population characteristics include study of population density, growth rate and social compositions, and worker status. The study has been done to analyse reasons and effects of spatial and temporal distribution of population; the spatial aspects of social composition, i.e. sex ratio, literacy rate and worker’s classification that were portrayed for 2011 census. The secondary sources of data of two census years 2001 and 2011 are collected to portray different population characteristics at ward level. Sex ratio is considered as an important parameter for determining the growth of population, social condition of the society, quality of life etc. Spearman’s rank difference method has been used to find the coefficients of correlation between literacy and sex ratio, and literacy and working population of the city. Certain relevant and pragmatic conclusions are derived from the discussion.